Operation of the Airborne 355-nm High Spectral Resolution and Doppler Lidar LNG - Bruneau D.; Pelon J.; Blouzon F.; Cazenave Q.; Collomb H.; Irbah A.; Mariscal J-F; Delanoë J. (EPJ Web of Conferences, 2020)
High spectral resolution lidar (HSRL) are known to offer capabilities of separating attenuated aerosol and molecular backscattering so that particle extinction and backscattering can be separately retrieved. UV operation provides high energy in eye-safety conditions. Further to that, it could be important for most meteorological or environmental studies to get wind measurements at the same time. LNG is now the only HSR Doppler Lidar (HSRDL) system capable of this. Results obtained during ground-based and airborne measurements show that the backscatter and extinction coefficients at 355 nm can be measured with a relative precision better than 10% (adjusting altitude and time resolution from 60 m to 240 m and 30s to 2mn, respectively) in aerosol layers of 0.5 10−6 m−1 sr−1 backscatter coefficient from ground and aircraft. The same relative precision is obtained in cirrus clouds of a 10−5 m−1 sr−1 backscatter coefficient. The capacity of the system to perform wind velocity measurements has also been demonstrated with precisions in the range of 1 to 2 ms−1 in same conditions. We present the main characteristics and illustrate observational capabilities from ground-based and airborne measurements.